Evidence that the 50-kDa substrate of brefeldin A-dependent ADP-ribosylation binds GTP and is modulated by the G-protein beta gamma subunit complex. - Di Girolamo, M (1995)
Brefeldin A, a fungal metabolite that inhibits membrane transport, induces the mono(ADP-ribosyl)ation of two cytosolic proteins of 38 and 50 kDa as judged by SDS/PAGE. The 38-kDa substrate has been previously identified as glyceraldehyde-3-phosphate dehydrogenase (GAPDH). We report that the 50-kDa BFA-induced ADP-ribosylated substrate (BARS-50) has native forms of 170 and 130 kDa, as determined by gel filtration of rat brain cytosol, indicating that BARS-50 might exist as a multimeric complex. BARS-50 can bind GTP, as indicated by blot-overlay studies with [alpha-32P]GTP and by photoaffinity labeling with guanosine 5'-[gamma-32P] [beta,gamma-(4-azidoanilido)]triphosphate. Moreover, ADP-ribosylation of BARS-50 was completely inhibited by the beta gamma subunit complex of G proteins, while the ADP-ribosylation of GAPDH was unmodified, indicating that this effect was due to an interaction of the beta gamma complex with BARS-50, rather than with the ADP-ribosylating enzyme. Two-dimensional gel electrophoresis and immunoblot analysis shows that BARS-50 is a group of closely related proteins that appear to be different from all the known GTP-binding proteins.